Exploring the Characteristics of Mass Media Coverage: A Critical Discourse Analysis Study to Improve Digital Literacy - Yosawati, Rezky Alviniyanti; Ansoriyah, Siti; Anoegrajekti, Novi (Electronic Journal of Education, Social Economics and Technology, 2024)
Mass media as news producers can be classified into two groups: incorporated and unincorporated mass media. Although both can produce news with the same topic according to actual conditions, the narratives built are not the same. In response to this, readers' criticality is needed to sort out objective and not tendentious information so that the information does not trigger social conflict in the community. This study aims to compare the characteristics of news discourse of the two mass media groups with a critical discourse analysis approach within the framework of media literacy. Data on legal mass media is based on data on the dewanpers.or.id page. The results show that there are obvious differences from the point of view of linguistic features between the news of digital mass media with legal status and those without legal status. This research is expected to be a policy reference for the government in fostering mass media and society.